Postpartum depression among women: a systematic review of prevalence, risk factors, and maternal outcomes - Rajendran, Vasuki R.; K., Mangayarkarasi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Postpartum depression (PPD) was the most common psychiatric complication that followed childbirth, but it often remained undiagnosed and untreated across many regions of the world. Its prevalence differed greatly, depending on the characteristics of the population studied, the screening tools used, and the influence of cultural context. This review, conducted under PRISMA guidelines, synthesized findings from 10 peer-reviewed studies released between 2012 and 2023. Searches were conducted in PubMed, Scopus, and Web of Science. Only original observational studies evaluating PPD prevalence, identifying risk factors, and reporting maternal outcomes with validated tools were included. Extracted information covered study aspects, prevalence values, and risk factors, and narrative synthesis was applied. In the 10 included studies, which had sample sizes between 350 and 12,198, the prevalence of PPD ranged from 7.3% to 30.3%. Recurrent risk factors identified were low education, unemployment, unmarried status, cesarean birth, unplanned pregnancy, preterm delivery, absence of breastfeeding plans, low Apgar scores, poor partner support, and past psychiatric conditions. Protective influences included higher education, partner support, and effective breastfeeding. PPD was recognized as a worldwide maternal health challenge, with prevalence rates reported up to 30%. The review stressed the need for routine screening programs, culturally responsive interventions, and policies aimed at social determinants of maternal well-being.